Management practices as risk factors for the presence of bulk milk antibodies to Salmonella, Neospora caninum and Leptospira interrogans serovar hardjo in Irish dairy herds. (24th March 2014) - O' Doherty, E.; Berry, D. P.; O' Grady, L.; Sayers, R.
<x content-type="archive" xml:space="preserve">Abstract</x> A survey of management practices in 309 Irish dairy herds was used to identify risk factors for the presence of antibodies to Salmonella, Neospora caninum and Leptospira interrogans serovar hardjo in extensively managed unvaccinated dairy herds. A previous study documented a herd-level seroprevalence in bulk milk of 49%, 19% and 86% for Salmonella, Neospora caninum and leptospira interrogans serovar hardjo, respectively in the unvaccinated proportion of these 309 herds in 2009. Association analyses in the present study were carried out using multiple logistic regression models. Herds where cattle were purchased or introduced had a greater likelihood of being positive to leptospira interrogans serovar hardjo (P<0.01) and Salmonella (P<0.01). Larger herds had a greater likelihood of recording a positive bulk milk antibody result to leptospira interrogans serovar hardjo (P<0.05). Herds that practiced year round calving were more likely to be positive to Neospora caninum (P<0.05) compared to herds with a spring-calving season, with no difference in risk between herds that practiced split calving compared to herds that practiced spring calving. No association was found between presence of dogs on farms and prevalence of Neospora caninum possibly due to limited access of dogs to infected materials including afterbirths. The information from this study will assist in the design of suitable control programmes for the diseases under investigation in pasture-based livestock systems.